Success factors and barries in the implementation of load-bearing masonry system: the case study of construction firms in Malaysia - Ramli, Azlinda; Abdullah, Che Sobry; Mohd Nawi, Mohd Nasrun; Baluch, Nazim Hussain; Bahaudin, Ahmad Yusni (ExcelingTech Publishers, 2016)
This study addresses the success factor and barriers in the implementation of load-bearing masonry (LBM) system. The case study is conducted through an interview to explore the situation of success factors and the barriers of implementation LBM system between the construction companies in Malaysia. The finding indicates the success factors for implementation of the LBM system in the construction companies are: organizational resources, usefulness, less maintenance, reduce construction time and cost, and these factors are consistent with the previous literature finding. Furthermore, the barriers of the implementing LBM system are due to lack of knowledge among the industry players and logistics issue.Thus, these success factors should be considered for the other companies that are interested to use the LBM system in their future projects. Additionally, to encourage policy makers into considering these factors in future action plans to enhance the adoption of LBM systems in the construction industry.